1991
DOI: 10.1007/bf00033912
|View full text |Cite
|
Sign up to set email alerts
|

Rhizome induction and plantlet regeneration of Cymbidium goeringii from flower bud cultures in vitro

Abstract: Apical flower buds of Cymbidium goeringii Reichenbach ill. (ca 2 mm long) excised from inflorescences (ca 5 cm long) were explanted on modified Murashige & Skoog medium (=MS medium) supplemented with N6-benzyladenine (BA) and ~-naphthaleneacetic acid (NAA). Within 107 days of culture, swelling growth, chlorophyll synthesis, and subsequent rhizome differentiation were observed. MS medium containing 0.1 mg 1 1 BA and 10 mg 1-1 NAA was found to be optimal for initiating rhizome development and subsequent plantlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 5 publications
4
19
1
1
Order By: Relevance
“…Similar explants of Cymbidium (Kim and Kako 1984;Shimasaki and Uemoto 1991) Phalaenopsis, Phragmipedium (Fast 1980a, b), and other orchids were cultured subsequently (for reviews, lists of orchids that were cultured and procedures, see Arditti and Ernst 1993a;Arditti and Krikorian 1996;Arditti 2008). …”
Section: Stemsmentioning
confidence: 99%
“…Similar explants of Cymbidium (Kim and Kako 1984;Shimasaki and Uemoto 1991) Phalaenopsis, Phragmipedium (Fast 1980a, b), and other orchids were cultured subsequently (for reviews, lists of orchids that were cultured and procedures, see Arditti and Ernst 1993a;Arditti and Krikorian 1996;Arditti 2008). …”
Section: Stemsmentioning
confidence: 99%
“…Shoot tip culture of Cymbidium bench-marked the onset of tissue culture per se (Morel, 1960). Since then protocols for the tissue culture of Cymbidium by using flower stalks (Wang, 1988), pseudobulbs (Shimasaki and Uemoto, 1990), flower buds (Shimasaki and Uemoto, 1991), shoot tips (Morel, 1960(Morel, , 1964Wimber, 1963;Sagawa et al, 1966;Ueda and Torikata, 1968;Kim and Kako, 1984) and PLBs (Begum et al, 1994b;Tanaka, 2004a, 2004b;Huan et al, 2004) have been described. Studies on callus induction are scarcer, attributed to their slow growth and necrotic tendency (Begum et al, 1994a).…”
Section: Introductionmentioning
confidence: 98%
“…It was documented that shoot formation from the rhizomes of these species was affected by some factors such as plant growth substances (Chung et al, 1985b;Hasegawa et al, 1985;Lee et al, 1986;Shimasaki and Uemoto, 1990;Paek and Yeung, 1991;Shimasaki and Uemoto, 1991;Chang and Chang, 1998;Chang and Chang, 2000a;Chang and Chang, 2000b;Lu et al, 2001), sucrose (Paek and Yeung, 1991), active charcoal (Chung et al, 1985a;Paek and Yeung, 1991;Chang and Chang, 2000b), liquid culture (Hasewaga et al, 1985) and illumination (Chung et al, 1985a;Paek and Yeung, 1991), of which, the cytokinin/auxin ratio in medium was the most important one. Usually, lower cytokinin/auxin ratios promoted the growth and propagation of rhizomes and higher ratios stimulated shoot initiation (Chung et al, 1985b;Hasegawa et al, 1985;Lee et al, 1986;Shimasaki and Uemoto, 1990;Paek and Yeung, 1991;Shimasaki and Uemoto, 1991;Chang and Chang, 1998;Chang and Chang, 2000a;Chang and Chang, 2000b;Lu et al, 2001), and in the cases of C. faberi (Hasegawa et al, 1985), C. ensifolium var. misericors (Chang and Chang, 2000b), C. kanran (Shimasaki and Uemoto, 1990) and C. sinense (Chang and Chang, 2000b), cytokinins were essential for the rhizomes to initiate shoots.…”
mentioning
confidence: 97%
“…Since then, in vitro seed germination protocols have been established for lots of orchid species (Arditti, 1977). Compared with epiphytic orchids, terrestrial Cymbidium species were thought to be difficult to regenerate in vitro either from seeds or from tissues (Shimasaki and Uemoto, 1991), but plant regeneration from the seeds of several high-value terrestrial Cymbidium species distributed in eastern Asia were successfully achieved by optimizing culture conditions, especially by monitoring the levels of plant growth substances in media (Chung et al, 1985a;Chung et al, 1985b;Hasegawa et al, 1985;Lee et al, 1986;Shimasaki and Uemoto, 1990;Paek and Yeung, 1991;Shimasaki and Uemoto, 1991;Chang and Chang, 1998;Chang and Chang, 2000a;Chang and Chang, 2000b;Lu et al, 2001). In the case of C. faberi, Hasegawa et al (1985) investigated that the effects of BA level, rhizome length, mechanical treatment and liquid shaking culture on the shoot formation from the seed-derived rhizomes and found that BA was essential for the rhizomes to form shoots and the most reasonable concentration of BA for the shoot formation and shoot growth was 0.1-1 mg l )1 .…”
mentioning
confidence: 99%